De novo assembly of the complex genome of Nippostrongylus brasiliensis using MinION long reads - Eccles, David (BMC Biol, 2018)
BACKGROUND: Eukaryotic genome assembly remains a challenge in part due to the prevalence of complex DNA repeats. This is a particularly acute problem for holocentric nematodes because of the large number of satellite DNA sequences found throughout their genomes. These have been recalcitrant to most genome sequencing methods. At the same time, many nematodes are parasites and some represent a serious threat to human health. There is a pressing need for better molecular characterization of animal and plant parasitic nematodes. The advent of long-read DNA sequencing methods offers the promise of resolving complex genomes. RESULTS: Using Nippostrongylus brasiliensis as a test case, applying improved base-calling algorithms and assembly methods, we demonstrate the feasibility of de novo genome assembly matching current community standards using only MinION long reads. In doing so, we uncovered an unexpected diversity of very long and complex DNA sequences repeated throughout the N. brasiliensis genome, including massive tandem repeats of tRNA genes. CONCLUSION: Base-calling and assembly methods have improved sufficiently that de novo genome assembly of large complex genomes is possible using only long reads. The method has the added advantage of preserving haplotypic variants and so has the potential to be used in population analyses. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12915-017-0473-4) contains supplementary material, which is available to authorized users.